(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
The interconnection of behavioral repertoires is a process related to creativity and the majority of empirical studies were conducted with non-human animals. The present study aims to produce the interconnection of repertoires in humans in a virtual environment, using the “puzzle creator” tool from the Portal 2®, a commercial videogame. A problem situation was created in the game environment, and participants then controlled a character in this three-dimensional virtual environment, from a first-person perspective. The sample consisted of 5 subjects, and none of these solved the problem situation in a pretest. However, after pre-requisite training of task-solving repertoires, 4 of the 5 participants solved the final task. It is concluded that the game Portal 2 can be an economical and versatile tool for the study of human interconnection of repertoires.